Changing patterns of party unity in the Knesset: The consequences of the Israeli anti-defection law. (September 2019) - Nikolenyi, Csaba
This article explores the consequences of the Israeli anti-defection law for the rate and timing of party switching in the Knesset. Its central finding is that while the anti-defection law has failed to act as a strong deterrent against party exits and defections, it (i) moved defections to the immediate pre-electoral period and (ii) encouraged collective party switching via the formation of new party groups as opposed to solo defections. While these effects can be directly attributed to the incentives that are generated by the legislation, the Israeli case holds an important implication for the comparative study of anti-defection laws: such laws may not improve legislative party unity if there are other institutions, such as the electoral system and candidate selection practices, that have a countervailing effect and incentivize party exit.